Siklus Akuntansi, Transparansi, Dan Akuntabilitas Atas Penggunaan Dan Pertanggungjawaban Keuangan Dana BOS Di SDIT X Di Depok, Jawa Barat - Yumniati Agustina (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2016)
Investigation in various regions in Indonesia found indications of the alleged fraud that result from unccountable use and management of BOS funds. Among the findings, including payments that do not fit the technical guidelines, no accountability report, and the use of funds with unaccountable receipt. In the Regulation of the Minister of Education and Culture of the Republic of No. 161/2014, stated that: BOS is a government program that is basically forfunding the nonpersonnel operating costs of the primary education as the implementer of compulsory education program. The purpose of this study were (1) to analyze the accounting cycle and financial accountability for the use of BOS funds in the 2015, (2) to analyze the compliance of the accounting cycle and financial accountability of the BOS funds, (3) to analyze the transparency and accountability of BOS fund’s reports. The observed elementary school is SDIT X in Depok, West Java. Result shows that they do not fully compliance to the appropriate regulatory technical guidelines. On the other hand, the transparency and accountability issues show that: (1) BOS Management Team, Teachers Council and School’s Committee’s involvement in the BOS fund management, and (2) evaluation and comparison of the final report of prior periods, so that transparency and accountability of the use and management of BOS funds can be improved.